PENGARUH LIKUIDITAS, PROFITABILITAS DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Sektor Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023) - Noni Nopita; Rizca Puspita Devi (Economicus, 2024)
This research aims to determine the influence of Liquidity, Profitability, and Activity on Company Value in the textile and garment sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This study is a quantitative research. The population used consisted of 22 companies in the textile and garment sector listed on the Indonesia Stock Exchange. The sample in this study was selected using purposive sampling method, resulting in 6 companies being chosen as the research objects. The data analysis method used is multiple linear regression analysis using SPSS. The results of this study indicate that partially Liquidity (CR) and Profitability (ROA) do not affect the Company Value of textile and garment sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Meanwhile, Activity (TATO) has a positive and significant effect on the Company Value of textile and garment sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Simultaneously Liquidity (CR), Profitability (ROA), and Activity (TATO) have a significant effect on the Company Value of textile and garment sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023 with a significance level of 0.001<0.05.